(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
This article examines certain aspects of using an electronic language corpus in foreign language teaching. It highlights the advantages of utilizing corpus data in the process of language learning, particularly in studying its lexical and grammatical features. The article identifies practical tasks that regular work with corpus data helps to address, including not only subject-specific and methodological issues but also pedagogical, translation-related, and other challenges. The author shares their experience in using corpus data in English language teaching. A brief overview of Mark Davies’ Corpus of Contemporary American English (COCA) is provided as the most extensive and widely used corpus available in open access. Additionally, the author presents recommendations for using corpus data of contemporary American English in teaching English. Research Objective is to explore the features of using electronic language corpora in teaching English as a foreign language and to demonstrate the advantages of applying corpus data for studying the lexical and grammatical characteristics of the language. Relevance and Scientific Novelty: This study presents a modern approach to teaching English through the use of corpus data, enabling work with authentic language examples and enhancing the understanding of lexical and grammatical structures.